Management practices and the quality of primary care - Jannis Angelis; Anna Häger Glenngård; Henrik Jordahl (Research Institute of Industrial Economics (IFN), 2017)
Using the World Management Survey method, we map and analyse management quality in Swedish primary care centres. On average, private providers have higher management quality than public ones. We also find that centres with a high overall social deprivation among enrolled patients tend to have higher management quality. Regarding quality of care, we find that management quality is positively associated with accessibility, but not with patient reported experience.
Keywords: H42; I11; L23; L33; 330; Management quality; Primary care; Quality of care; Accessibility; World Management Survey